The Impact of Case Study-Based Learning with SPSS on Student Outcomes at Medan State Polytechnic - Harizahayu Harizahayu; Koko Hermanto; Ratna Yuniarti (RANGE: Jurnal Pendidikan Matematika, 2025)
This study intends to create a statistical learning model by integrating theory and practice, using the SPSS software application with case studies of problem solving in Computer Engineering and Informatics students at the Medan State Polytechnic. The design of this study began with a literature review before making lesson plans with the task of making teaching materials and providing content to students. Besides that, after the writer led the discussion, he was given the task of determining cases based on the subjects chosen by the students according to their interests. In this study there were 70 students who participated as the research sample. NONCase and STDCase both have standard deviation values ​​of 1.62001 and 1.84694, respectively. Because the average learning outcomes of NONCase 74.2571 and STDCase 78.8857 show that descriptively there are differences between NONCase-based learning and case study/STDCase-based learning. The NONCase method and the STDCase learning method using the SPSS program have a significant linear relationship between the variables, according to case study-based research. Using the formula F count = 0.982 > F table = 1.507 It can be concluded that there is a significant linear relationship between the mastery of the STDCase learning approach and the SPSS program because F count is smaller than F table